Financial Feasibility Analysis Of Regional Public Companies (Perumda) Puspahastama Purbalingga District - Putranto, Afif Hendri; Anwar, Seful; Suprapto, Suprapto (Akademi Komunitas Perkebunan Yogyakarta, 2024)
This research is entitled Financial Feasibility Analysis of the Puspahastama Regional Public Company, Purbalingga Regency. The objectives of this research are 1) Analyze the level of financial feasibility of Perumda Puspahastama 2) Analyze the level of sensitivity of Perumda Puspahastama to changes in benefits and costs. This type of research is quantitative which is presented in tabular form, grouping and classifying data. The research results show that Perumda Puspahastama is feasible with a positive NPV value at a discount factor of 9%, namely Rp. 9,210,001,190, the IRR is greater than the applicable interest rate (9%) namely 35.32%, and the Net B/C Ratio is greater than one, namely 3.58%. Sensitivity analysis was declared feasible with four main variables which included a 20% decrease in income, a 12% increase in grain prices accompanied by a 12% increase in income, a 10% increase in diesel prices with an increase in income and costs of 2%, variables increased by 13 % which with an increase in income of 13%. Meanwhile, the combined results are still decent with a decrease in income of 20%, an increase in grain prices of 12%, diesel prices of 10%, and variable costs of 13%